1997
DOI: 10.1083/jcb.137.7.1581
|View full text |Cite
|
Sign up to set email alerts
|

Human Bcl-2 Reverses Survival Defects in Yeast Lacking Superoxide Dismutase and Delays Death of Wild-Type Yeast

Abstract: We expressed the human anti-apoptotic protein, Bcl-2, in Saccharomyces cerevisiae to investigate its effects on antioxidant protection and stationary phase survival. Yeast lacking copper-zinc superoxide dismutase (sod1Δ) show a profound defect in entry into and survival during stationary phase even under conditions optimal for survival of wild-type strains (incubation in water after stationary phase is reached). Expression of Bcl-2 in the sod1Δ strain caused a large improvement in viability at entry into stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(131 citation statements)
references
References 34 publications
5
126
0
Order By: Relevance
“…This idea is consistent with the observation that overexpression of human Bcl-2 improves survival of yeast lacking superoxide dismutase (Longo et al, 1997). Furthermore, human Bcl-2 and Bcl-xL can replace the anti-death function of yeast Fis1, and also inhibit yeast mitochondrial fragmentation following a death stimulus .…”
Section: Yeast As Models Of Mitochondrial Cell Death In Mammalssupporting
confidence: 88%
“…This idea is consistent with the observation that overexpression of human Bcl-2 improves survival of yeast lacking superoxide dismutase (Longo et al, 1997). Furthermore, human Bcl-2 and Bcl-xL can replace the anti-death function of yeast Fis1, and also inhibit yeast mitochondrial fragmentation following a death stimulus .…”
Section: Yeast As Models Of Mitochondrial Cell Death In Mammalssupporting
confidence: 88%
“…Previous work by Longo et al [12] has shown that yeast cells harboring Bcl-2 have enhanced survival ability. Under stationery phase death conditions, yeast cells expressing Bcl-2 live considerably longer than wild-type strains.…”
Section: Discussionmentioning
confidence: 97%
“…S. cerevisiae is sensitive both to H 2 O 2 and to superoxide-generating agents [9][10][11]. Yeast deletion mutants of antioxidant genes such as catalase, superoxide dismutase, and cytochrome c peroxidase result in strains hypersensitive to lethal effects of oxidative stresses relative to isogenic wild-type cells [1,5,12]. Growth under anaerobic condition does not exhibit such sensitivity to these mutants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fasting has been demonstrated to selectively protect normal cells and mice, but not cancerous cells against oxidants and common chemotherapeutic agents (Longo et al, 1997;Raffaghello et al, 2008). In cancer patients, preliminary data suggest that fasting is not only safe and feasible, but may also be effective in reducing common side-effects associated with chemotherapy (Safdie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%